MODIFIKASI SENSOR KECEPATAN ANGIN BEDA SUHU BERBASIS MIKROKONTROLER DENGAN TRANSMISI JARAK JAUH SEBAGAI PENGUKUR POTENSI PEMBANGKIT LISTRIK TENAGA ANGIN - Harnawan, A. A.; Assadat, A. L.; Jannah, F. N. (Jurnal Pendidikan Fisika Indonesia, 2009)
Modifikasi sensor kecepatan angin beda suhu bertujuan untuk memperbaiki kinerja sensor dengan menstabilkan prosespenginderaan kecepatan angin dan transmisi data jarak jauh, yang dilakukan dengan menambahkan mikrokontroler AT89S52sebagai basis operasi, rangkaian transmisi jarak jauh dengan jarak 15 m menggunakan level data RS232 dan juga dilengkapidengan rangkaian ADC0808 terkendali mikrokontroler, pada akhirnya sensor dapat berfungsi lebih baik. Pengujian lapangansensor menunjukkan kecepatan angin di sekitar Laboratorium Pengembangan Fisika berfluktuasi antara 0,25 m/s sampai 0,35m/sÃÂ Detector made in this study is a black box camera made of aluminum. This detector is made of aluminum plate 2-mm thick, a box of(20x15x30) cm, with the following components: the detector panels, paper, film / photography, and sources of ionizing radiation withradiation. Interaction between ionizing radiation and film paper produces a shadow on the paper trail showing blackened after beingwashed. The blackening of radiation attenuation, absorption with at least translucent material produces a shadow on the paper film,with variation of exposure time, the absorbent material and distance, the detector can be using ionizing radiation submer qualitativetests. Camera conclusively prove can be used as a learning tool in the core content and radioactivity in high school.Keywords: detector, ionizing radiation, learning tool